Morfogénesis del gametotito del helecho Thyrsopteris elegans (Filicales: Thyrsopteridaceae) - Pérez-García, Blanca; Mendoza, Aniceto; Riba, Ramón; Ricci, Marcia (Revista de Biología Tropical, 1996)
As part of a series about Neotropical and related ferns, the morphogenetic development of Thyrsopteris elegans, an endemic species of the Archipelago Juan Fernandez Chile, is presented. The spores are tetrahedral-globose, trilete, homosporous, non-green. The germination of the spores is of the Cyathea-type and the prothallial development corresponds to the Drynaria-type. The antheridia and the archegonia are typical of the leptosporangiate ferns. The sporophyte appears 200 days after sowing. Apogarny was not observed in this species